THE INTERPRETATION OF DOUBLE BURDEN OF WOMEN: A Comparison between al-Misbah and al-Lu’lu’ wa al-Marjân fî Tafsîr al-Qur’ân - Nafilah Sulfa (Islamuna: Jurnal Studi Islam, 2020)
One of the factors that causes women to experience gender inequality so that they are not equal to men is the gender-biased interpretation of religious texts. Applying interpretive approach and comparative method as well as the theory of liberal feminism and double movement, this article discusses three issues, namely: (a) double burden for women in the Qur’an; (b) the interpretation of M. Quraish Shihab in al-Misbah and Karîmân Hamza in al-Lu'lu 'wa al-Marjân fî Tafsîr al-Qur’ân regarding verses of the Qur’an containing double burden for women; and (c) the assumption that the gender of the interpreter could result in a gender-biased interpretation. This research shows that Islam comes on a mission to bring about equality between mankind. Shihab’s interpretation is more accommodating to women’s interests than that of Hamza’s, while Hamza’s interpretation is more patriarchal. Preference to certain sexes is not always related to gender equality in the interpretation of the Qur’an, so the assumption that one of the factors causing women to experience gender inequality is the gender-biased interpretation of religious texts simply because the majority of interpreters are male can not be justified.[Salah satu faktor penyebab kaum perempuan mengalami ketimpangan gender, sehingga mereka belum setara adalah interpretasi teks-teks agama yang bias gender. Dengan pendekatan tafsir, metode komparatif dan teori feminisme liberal serta double movement, artikel ini mendiskusikan tiga persoalan, yaitu: (a) double burden perempuan dalam Al-Qur’an; (b) penafsiran M. Quraish Shihab dalam al-Misbah dan Karîmân Hamzah dalam al-Lu’lu’ wa al-Marjân tentang ayat double burden bagi perempuan; dan (c) asumsi bahwa jenis kelamin mufasir menimbulkan penafsiran bias gender. Penelitian ini menunjukan Islam membawa misi kesetaraan manusia. Penafsiran Shihab lebih akomodatif terhadap kepentingan perempuan, sedangkan penafsiran Hamzah lebih bias patriarkal. Keberpihakan pada jenis kelamin tertentu tidak selalu berhubungan dengan kesamaan jenis kelamin dalam penafsiran Al-Qur’an, sehingga asumsi salah satu faktor penyebab kaum perempuan mengalami bias gender adalah interpretasi teks agama yang bias gender karena mayoritas mufasir adalah laki-laki tidak dapat dibenarkan]